Teacher’s Strategies in Teaching English Vocabulary at Sixth Grade Students of Raudhatul Jannah Islamic Elementary School - Inaya, Rifka; Nurdin; Zulfikri (Indonesian Journal Publisher, 2025)
The aim of this research was to identify the strategies used by the teacher in teaching English vocabulary to sixth-grade students at Raudhatul Jannah Islamic Elementary School, to explore how these strategies were implemented, and to examine the challenges faced by the teacher during the teaching process. This study employed a qualitative approach to answer the formulated research questions. The instruments used in collecting the data were observation, interviews, questionnaire and document review. The findings revealed that the teacher applied four main strategies in teaching vocabulary: (1) using pictures, (2) games, (3) song, and (4) making task. The implementation of these strategies involved various interactive and student-centered activities such as visual aids, singing, sentence construction, and game-based learning. However, the study also found that the teacher faced several challenges in the teaching process, including students’ lack of motivation (1), Insufficient Time (2), and students’ limited vocabulary (3). Despite these obstacles, the teacher made continuous efforts to adapt teaching methods and support student learning.